Возможность использования низкообогащенного топлива в реакторе ИРТ-Т; Известия вузов. Физика; Т. 55, № 11-2 - Наймушин А. Г. Артем Георгиевич; Чертков Ю. Б. Юрий Борисович; Луханов А. К. Александр Констанвич; Лебедев И. И. Иван Игоревич (2012, 2012)
Заглавие с экрана